PENGARUH STRATEGI SQ4R TERHADAP KETERAMPILAN MEMBACA SEKILAS DI SEKOLAH DASAR: PENGARUH STRATEGI SQ4R TERHADAP KETERAMPILAN MEMBACA SEKILAS DI SEKOLAH DASAR - sry apfani (LP2M Universitas Adzkia, 2021)
This research is motivated by problems related to the low skim reading skills of students. This can be seen in students' interest in reading, there are still some students who do not understand punctuation marks, students are still not quite right in answering some questions related to the content of reading, students find it difficult to understand the content of the text, this is because skimming skills are still low, and students less motivated to read text by skimming, because skimming skills are still low. This study aims to determine the effect of the SQ4R strategy on skimming skills in class V SDN 35 Parak Karakah, Padang City. This research includes experimental research using Quasy Experiment Design with The Nonequivalent Group Pretest-Posttest Design. The subjects of this study were all fifth grade students in the second semester of SDN 24 Kalumbuk, Padang City, which consisted of 2 classes totaling 45 people. Class VA as the experimental class and class VB as the control class. The experimental class was treated using the Survey, Question, Read, Reflect, Recite And Review (SQ4R) strategy on skimming skills while the control class used conventional learning. Based on the data analysis, the results of the test on the data from the sample class are normally distributed and homogeneous. Subsequently, a hypothesis test was carried out with a t-test showing tcount = 3.625 and ttable = 1.68107, where tcount is greater than ttable then H0 is rejected and H1 is accepted with the conclusion that